HISTOPATHOLOGICAL OF DIABETES MELLITUS WHITE RAT TESTICLE AFTER GIVEN MORINGA LEAF EXTRACT - Jannah, Raodatul; Setiasih, Ni Luh Eka; Suastika, Putu (Buletin Veteriner Udayana, 2018)
This study aimed to determine changes in testicular histopathological of the rat strain wistar diabetes mellitus experienced. This study used 24 white rats ( Rattus norvegicus ) strain Wistar which were divided into six groups: administration of Moringa oleifera leaves P1 (extract dose 0 mg/kg bw) , P2 (100 mg/kg bw) , P3 (200 mg/kg bw), P4 (300 mg/kg bw) , P5 (400 mg/kg bw)  and P6 ( 500 mg/kg bw) . In the end of administration, the diabetic Wistar rats were sacrificed and their testes were taken to make the histopathological preparations using haematoxylin and eosin staining. The observed variables are fat degeneration and necrosis. The results show that moringa leaves can improve histopathology testis structure of diabetes mellitus white rats. Extract of Moringa leaves (Moringa oleifera ) dose of 400 mg/kg body weight has the best effect repair damage to the histopathological testis.